Consumer Perceptions on Plastic Bags Usage: An Empirical Research in Kuala Lumpur, Malaysia - Yow, Pei Yee (2013)
In today world, the packaging industry offers numerous types of pouching products to food and beverage industries, healthcare industries and households. Pouching products are widely used and seems it has taken an indispensable role in our daily life. Pouching products are easily found in Malaysia to parcel grocery, purchased stuffs, and food. This practice has raises solid waste disposal issue as well. A study by Jayaraman et al. (2011) found more than 62 percent of the consumers are using plastic bags for storing stuffs daily or weekly because of its easy availability, weight convenience and cost effectiveness. Malaysian Government has enforced regulations and campaign like ‘No Plastic Bag Day’ to reduce the plastic bags usage with aiming to reduce the environmental impact caused by plastics. On the other hand, consumers are optimistic that the environmental and health hazards from the use of plastic bags would have a positive impact in the future. Hence, it raised an interest for researcher to conduct an empirical study regards consumer perceptions on plastic bags usage as well as to examine the factors that would influence their perceptions.